SANTRI AND ABANGAN AFTER A HALF CENTURY OF CLIFFORD GEERTZ - Amanah Nurish (Universitas Islam Negeri Ar-Raniry, 2021)
This research paper analyzes the religious phenomenon of culture in Modjokuto or Pare, where Geertz carried out his thesis on the